Biomimetic Integrated Nanozyme for Flare and Recurrence of Gouty Arthritis - Rui Wang; Tongyao Liu; Xinhong Li; Enhao Lu; Yiting Chen; Kuankuan Luo; Tao Wang; Xueli Huang; Zhiwen Zhang; Shilin Du; Xianyi Sha (Elsevier, 2024)
Flare and multiple recurrences pose significant challenges in gouty arthritis. Traditional treatments provide temporary relief from inflammation but fail to promptly alleviate patient pain or effectively prevent subsequent recurrences. It should also be noted that both anti-inflammation and metabolism of uric acid are necessary for gouty arthritis, calling for therapeutic systems to achieve these two goals simultaneously. In this study, we propose a biomimetic integrated nanozyme, HMPB-Pt@MM, comprising platinum nanozyme and hollow Prussian blue. It demonstrates anti-inflammatory properties by eliminating reactive oxygen species and reducing infiltration of inflammatory macrophages. Additionally, it rapidly targets inflamed ankles through the camouflage of macrophage membranes. Furthermore, HMPB-Pt@MM exhibits urate oxidase-like capabilities, continuously metabolizing locally elevated uric acid concentrations, ultimately inhibiting multiple recurrences of gouty arthritis. In summary, HMPB-Pt@MM integrates ROS clearance with uric acid metabolism, offering a promising platform for the treatment of gouty arthritis.